(untitled) (Journal of Health Sciences, 2025)
Introduction: When a parent is diagnosed with cancer, the psychological and social impact on their children can be profound. Teachers play a key role in supporting these children, yet limited research has examined school-based support in Japan. This study aimed to examine the awareness, perceptions, and support practices of elementary school teachers toward children with a parent who has cancer. Methods: A cross-sectional survey was conducted in Akita City. Demographic data included sex, age, parenting status, teaching years, and cancer/bereavement experiences. Teachers reported support experience and completed items on perception, knowledge, and anxiety. Teachers with support experience provided details about their most memorable case. Results: Among 500 questionnaires collected, 459 were analyzed. Of these, 270 teachers (54.0%) reported support experience. Support experience was significantly associated with being female, having children, and personal or familial cancer experience.Teachers with support experience showed higher perception, knowledge, and anxiety. Memorable cases involved initial contact with children of newly diagnosed parents. Support included observing behavior, promoting emotional expression. Conclusion: While teachers actively support affected children, personal factors and greater awareness were linked to increased anxiety. Enhancing teacher training and school–medical collaboration may improve support for children facing parental cancer.